Mainstreaming Equity in Education - Omoeva, Carina (FHI 360 Education Policy and Data Center / Education Equity Research Initiative, 2017)

5 features of a monitoring, evaluation and learning system geared towards equity in education - Omoeva, Carina (2018)
Wow do we operationalize equity in education, in the context of education development programming? This blog post from FHI 360’s R&E Search For Evidence blog presents five features necessary for a monitoring, evaluation and learning system to be geared towards equity in education.